Clinical quiz: The strawberry coloured breastmilk - Jamani, Nurjasmine Aida; Jahn Kassim, Puteri Shanaz (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2017)
A 33 year-old Para 1 complained of strawberry coloured breastmilk for 1 day duration while expressing her breastmilk on the left breast at work. She has been exclusively breastfeeding for the past 6 months and never encountered such incident before. She also felt pain over the left breast. However, there was no lump, nipple crack,abnormal nipple discharges or fever prior to that. She expressed her breastmilk using a double mechanical electric breastpump about five times a day lasting from 10 to 20 mintues per sesion since she returned to work.